Remuneration committee, board independence and top executive compensation - Chii-Shyan Kuo; Shih-Ti Yu (Journal of Risk and Financial Management, 2014)
In this study, we examine whether the levels and structures of top executive compensation vary discernibly with different levels of board independence. We also examine how the newly mandated adoption of the remuneration committee (RC) in Taiwan affects the board independence-executive pay relation. The mandatory establishment of RC for Taiwanese public firms, starting in 2011, is intended to strengthen the reasonableness and effectiveness of the executive compensation structure; thus, it is timely and of interest for practitioners and regulators to understand whether the establishment of RCs can effectively discipline top executive compensation policies. We first find that CEOs of firms that do not appoint independent directors have greater levels of annual pay than is the case for firms that have appointed independent directors, after controlling for the effect of CEO pay determinants. Second, we find that CEO pay for early RC adopters is more closely related to firm performance. Third, we find that the establishing of RCs may decrease CEO pay and enhance the pay-performance association, in particular for firms that have not appointed independent directors; however, this effect is not found to be statistically significant.
Keywords: J31; J33; M48; 330; remuneration committee; pay-performance relation; CEO compensation